The first tip-off [ the incredible story of the birth of the NBA - Rosen, Charles (McGraw-Hill professional, 2009)
The only book to tell the unbelievable true story of the NBA's tumultuous first season In "The First Tip-Off," veteran basketball writer Charley Rosen brings readers back to the NBA's humble beginnings, when a colorful cast of characters laid the foundation for the empire that is today's NBA. Basketball pioneers, like Red Auerbach, Chuck Connors, Ed Sadowski, Joe Fulks, and Peter "Press" Maravich-father of "Pistol Pete"-all play a role in a league of hard fouls, shady refs, meager facilities, and old school basketball. Featuring a Foreword by Los Angeles Lakers head coach Phil Jackson and exclusive interviews with the surviving players of that first season, Rosen weaves a fascinating and poignant portrait of a league struggling to gain a foothold in the American consciousness